2014
DOI: 10.4028/www.scientific.net/msf.778-780.859
|View full text |Cite
|
Sign up to set email alerts
|

Variant of Excess Current in 4H-SiC pn Structures

Abstract: Excess currents and defects were investigated in the 4H-SiC p+nn+ structures created by implantation. It was found that the principal p+n junction is shunted by several or multiple Schottky barriers connected in parallel to the principal pn junction and formed by a contact of Al on the surface of p+-layer with n-layer perhaps with participation of carbon coated surfaces of the pits or other defects. Amount and area of Schottky barriers vary for different pn structures, in connection with which vary as the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The conducting surface layer of the defect may be very thin and, discontinuous, and the electric contact of Al deposited on the surface of the p +layer with the n-layer through the defect may be difficult, unstable, and dependent on the applied voltage and temperature. Our EBIC and SE measurements confirmed that the depth of numerous defects may exceed the thickness of the p + -layer, this conclusion being valid not only for defects with the largest diameter (about 3 µm, as demonstrated by EPMA previously [1]), but also for defects with a substantially smaller size (1 µm, or even tenths of a micrometer, Fig. 2).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The conducting surface layer of the defect may be very thin and, discontinuous, and the electric contact of Al deposited on the surface of the p +layer with the n-layer through the defect may be difficult, unstable, and dependent on the applied voltage and temperature. Our EBIC and SE measurements confirmed that the depth of numerous defects may exceed the thickness of the p + -layer, this conclusion being valid not only for defects with the largest diameter (about 3 µm, as demonstrated by EPMA previously [1]), but also for defects with a substantially smaller size (1 µm, or even tenths of a micrometer, Fig. 2).…”
Section: Resultssupporting
confidence: 85%
“…Recently, we have reported on a study of excess currents and defects in 4H-SiC p + nn + structures fabricated by implantation [1]. It was found that the principal p + n junction is shunted by several or multiple Schottky barriers connected in parallel with the principal pn junction and formed by a contact of Al deposited on the surface of the p + -layer with the n-layer through pits.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of extra currents is reported in the literature [ 56 , 57 ] for as-fabricated leaky SiC p–n diodes and devices irradiated with electrons and protons (8.0 MeV). Extra currents are ascribed to epilayer defects and are due to shunt paths in parallel to the main p–n junction [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also it was found in a study of p + n structures fabricated by implantation that the principal p + n junction is shunted by natural, unintentional Schottky barriers that are connected in parallel to the principal pn junction and are formed by Al Materials Science Forum Vol. 858 deposited on the surface of the p + -layer and contacting with the n-layer via pits [6]. The possible relationship between the excess currents and epilayer defects of the 'hole' type was suggested in [5].…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, this indicates that the defects are in fact not solitary, having rather the form of a cluster of closely spaced defects, and then the size of a single defect can be estimated on the basis of the maximum values of R s . The defects may be of the 'hole' type as in [6], but, formally, defects of the type of pyramids, whiskers, columns, etc. are not improbable in our case of the comparatively thin epilayer.…”
Section: Resultsmentioning
confidence: 99%